Testicular adrenal rest tumors in boys with 21-hydroxylase deficiency, timely diagnosis and follow-up - Mirjana Kocova; Vesna Janevska; Violeta Anastasovska (My University, 2018)
Testicular adrenal rest tumors (TARTs) are found in 30-94% of adult males with congenital adrenal hyperplasia (CAH). We sought to explore TART appearance through yearly ultrasound examination of testes in young boys with CAH, and its association with metabolic control and genetic mutations.